Modern typography : an essay in critical history / Robin Kinross. - Kinross, Robin. (Hyphen Press, 2004)
"In a survey of developments since 1700, this book proposes a new understanding of modern typography: as something larger and more deeply rooted than a modernism of style. Rather, 'modern' is taken to imply an articulate consciousness of action. The book's treatment lays stress on debates over principle and explanations of practice. But full weight is given to the social, technical and material bases of the activity; and the argument is illustrated by freshly made photographs of items not often reproduced before. Sources of information are discussed and extensively listed. The book thus contributes on several levels: as a brisk narrative of historical development, as a springboard for further investigation, as a delineation of modern typography." "Published first in 1992, Modern typography is now issued in a revised and updated second edition."--Jacket.